2019
DOI: 10.1016/j.scog.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Cognition in schizophrenia improves with treatment of severe obstructive sleep apnoea: A pilot study

Abstract: Previous studies have shown that people with schizophrenia have high rates of Obstructive Sleep Apnoea (OSA). Despite this, intervention studies to treat OSA in this population have not been undertaken. The ASSET (Assessing Sleep in Schizophrenia and Evaluating Treatment) pilot study investigated Continuous Positive Airway Pressure (CPAP) treatment of severe OSA in participants recruited from a clozapine clinic in Adelaide. Participants with severe untreated OSA (Apnoea-Hypopnoea Index (AHI) > 30), were provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Thirdly, our data are observational and does not determine whether treatment of OSA co-morbid with schizophrenia improves cognitive measures, psychopathological outcomes, quality of life outcomes or cardiovascular risk factors. However, in an extension of this pilot study, we monitored the response to CPAP and found CPAP improved obesity and cognition when used in people with schizophrenia and severe OSA (published elsewhere) (Myles et al, 2019). Given the high prevalence of OSA in our pilot study and because CPAP treatment modifies these outcomes in general populations, further intervention studies are required to determine whether OSA treatment has any role in improving outcomes in this population.…”
Section: Discussionmentioning
confidence: 86%
“…Thirdly, our data are observational and does not determine whether treatment of OSA co-morbid with schizophrenia improves cognitive measures, psychopathological outcomes, quality of life outcomes or cardiovascular risk factors. However, in an extension of this pilot study, we monitored the response to CPAP and found CPAP improved obesity and cognition when used in people with schizophrenia and severe OSA (published elsewhere) (Myles et al, 2019). Given the high prevalence of OSA in our pilot study and because CPAP treatment modifies these outcomes in general populations, further intervention studies are required to determine whether OSA treatment has any role in improving outcomes in this population.…”
Section: Discussionmentioning
confidence: 86%
“…Symptoms of OSAS can resemble those of mental disorders and some medications used for severe mental disorders can exacerbate the symptoms of OSAS [31]. CPAP therapy for OSAS has been shown to improve cognitive impairment of schizophrenia patients [32], but has also resulted in manic symptoms in patients with bipolar disorder [33]. However, in one review, prevalence of OSAS was not increased in patients with schizophrenia, bipolar disorder or severe depression [34].…”
Section: Tablementioning
confidence: 99%
“…Fatigue and reduced concentration may result in lower productivity and increased workplace injuries. There is also increasing evidence that OSA accelerates the progression of Alzheimer's disease, and effective treatment of OSA may delay the onset of cognitive impairment and prevent psychiatric disorders 22–24 . There is a significant relationship between depression and OSA.…”
Section: Consequences Of Osamentioning
confidence: 99%
“…These conditions have shared risk factors, the symptoms overlap and there is bidirectional causality 25 . The prevalence and severity of OSA are increased in men with schizophrenia, 26 and treatment has been shown to be acceptable and beneficial 24 …”
Section: Consequences Of Osamentioning
confidence: 99%